Uporaba tehnologij sekvenciranja v farmakogenomiki - Janžič, Urška (Laboratorijska medicina, 2025)
Genetic variability in pharmacogenes, i.e. genes that affect absorption, distribution, metabolism, action and excretion of drugs, can significantly affect an individual’s response to a drug and, consequently, the effectiveness of treatment and the occurrence of adverse drug reactions. Despite the increasing number of evidence-based pharmacogenetic recommendations, pharmacogenetic testing is being only slowly introduced into clinical practice. One of the reasons is the limitation of the methods for determining pharmacogenetic variations. In clinical practice, targeted pharmacogenetic testing is most often performed, focusing only on a limited number of genetic variants and a few of the most frequently tested pharmacogenes. In recent years, research has focused on studying data obtained from whole exome or genome sequencing, which allows testing multiple variants simultaneously in a relatively short time and resolving complex pharmacophenotypes. A complex pharmacophenotype is defined by the presence of multiple pharmacogenetic variants and/or rare variants affecting drug metabolism or treatment response. Sequencing based methods enable identification of rare variants as well as large structural variants. The purpose of the paper is to present the advantages and disadvantages of targeted genotyping methods, whole exome and genome sequencing methods, and to highlight the importance of developing appropriate bioinformatics tools for efficient pharmacogenetic analysis, which would accelerate the translation of scientific findings into clinical practice.
Keywords: bioinformatska orodja; farmakogenetika; farmakogenomika; kompleksni farmakogeni; sekvenciranje naslednje generacije